Understanding sporting brands and entrepreneurship using netnography and social network analysis. (16th March 2023) - Fenton, Alex; Parry, Keith D.; Ahmed, Wasim; Chadwick, Simon
Social media offers a wealth of data to help inform and enlighten SMEs on a global scale. This study aims to demonstrate that data derived from social media networks can enhance entrepreneurship in SMEs, providing tools and guidance for entrepreneurs. We present a double case of two sporting SMEs and utilise a distinctive blend of quantitative data from social network analysis using NodeXL, followed by a qualitative analysis using netnography to gather data. We propose that using social media data in this way can create new insights for social commerce in order for SMEs to better understand consumer interactions.